2014
DOI: 10.1080/02726351.2014.938378
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Studies of Coal Fly Ash for Soil Application in Agriculture

Abstract: Coal fly ash procured from Guru Gobind Singh Super Thermal Power Plant, Ropar, Punjab, India, was analyzed for its mineralogical content and thermal stability by x-ray diffraction (XRD), thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and physicochemical properties. XRD studies showed that major crystalline phases observed were quartz (SiO 2 ) and aluminum silicon oxide (Al 4.52 Si 1 . 48 ) with macro-and microelement (N, P, K, Mg, Zn, S, and Fe). Fly ash showed thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the intensity of each peak increased with the increasing of density fractions, it indicated that the higher density fraction of oil shale it was, the higher content of each inorganic mineral in the oil shale sample, and it also indicated there was almost the same mineral composition in six density fractions of oil shale samples. By comparing these patterns we can note that the lower two present peaks with broad base lines, 13,14 typical of kerogen or coal patterns rich in organic matter and low inorganic mineral matter, whereas the upper four presented well-defined peaks in according with its high inorganic mineral matter content. 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the intensity of each peak increased with the increasing of density fractions, it indicated that the higher density fraction of oil shale it was, the higher content of each inorganic mineral in the oil shale sample, and it also indicated there was almost the same mineral composition in six density fractions of oil shale samples. By comparing these patterns we can note that the lower two present peaks with broad base lines, 13,14 typical of kerogen or coal patterns rich in organic matter and low inorganic mineral matter, whereas the upper four presented well-defined peaks in according with its high inorganic mineral matter content. 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…In the subsequent series, bentonite was added to the granulate (tests Nos. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and in the tests Nos. 14-19 waterglass (R140 CAS: 1344-09-8) was used as the binding liquid.…”
Section: Testing Methods and Materialsmentioning
confidence: 99%
“…1, 2) and at the bottom of the deposit (tests Nos. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Binding liquid flow rate Q was 0.83 m 3 /s (test No.…”
Section: Testing Methods and Materialsmentioning
confidence: 99%
See 2 more Smart Citations